Physical and chemical parameters and trace metal flux in water, soil and plant samples collected from industrial effluent affected areas in and around Dhaka city - Nahar, Kazi Kamrun; Alam, Sheikh Shamimul (Bangladesh Journal of Botany, 2018)
Water and soil samples were collected from five different industrial areas around Dhaka city namely, (i) Powertex Fashion Ltd., Gazipur (Textile), (ii) Shetu Pesticide Ltd., Savar (Pesticide), (iii) Salma Leather Industry, Hazaribagh (Tannery), (iv) Monno Ceramic Industries, Nayarhat, Dhamrai, (Ceramic) and (v) ACME Laboratories Ltd., Tulivita, Dhamrai (Pharmaceutical) where selected for this study. Two plants species viz. Colocasia esculenta (L.) Schott and Ipomoea aquatica Forssk. commonly growing in the industrial effluent affected areas were selected to observe the rate of heavy metal uptake. Dissolved oxygen (DO) was found below the permissible limit in all the affected areas (lowest 0.88 mg/l in tannery waste affected areas) indicating high amount of organic wastage discharge from tannery. Eight trace metals viz. arsenic, cadmium, nickel, iron, zinc, chromium, copper and lead were analysed for water, soil and plant samples. Arsenic and cadmium exceeded the permissible limit in water sample collected from all affected areas. Tannery waste affected area was found to be the most vulnerable area in respect to arsenic and chromium contamination. On the other hand, the highest amount of arsenic was found in the soil sample collected from pesticide affected area. The rate of heavy metal uptake in Colocasia esculenta (L.) Schott is much higher than Ipomoea aquatica Forssk. More heavy metals were accumulated in edible portion than roots of the plants.